2012
DOI: 10.1093/jxb/ers070
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in Citrus sinensis fruit tissues harvested from huanglongbing-infected trees: comparison with girdled fruit

Abstract: Distribution of viable Candidatus Liberibacter asiaticus (CaLas) in sweet orange fruit and leaves (‘Hamlin’ and ‘Valencia’) and transcriptomic changes associated with huanglongbing (HLB) infection in fruit tissues are reported. Viable CaLas was present in most fruit tissues tested in HLB trees, with the highest titre detected in vascular tissue near the calyx abscission zone. Transcriptomic changes associated with HLB infection were analysed in flavedo (FF), vascular tissue (VT), and juice vesicles (JV) from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
86
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 49 publications
15
86
1
1
Order By: Relevance
“…The knockout of UGT76B1 in Arabidopsis led to enhanced resistance to Pseudomonas syringae , but an increased susceptibility to Alternaria brassicicola [29]. In HLB-infected citrus trees, transcripts encoding different UGTs were modulated in leaves [17] and in fruit tissues infected with CaLas [18]. Among them, transcripts encoding a UGT73B3 were more abundant in infected leaves of the tolerant hybrid compared with Cleopatra, the susceptible citrus genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knockout of UGT76B1 in Arabidopsis led to enhanced resistance to Pseudomonas syringae , but an increased susceptibility to Alternaria brassicicola [29]. In HLB-infected citrus trees, transcripts encoding different UGTs were modulated in leaves [17] and in fruit tissues infected with CaLas [18]. Among them, transcripts encoding a UGT73B3 were more abundant in infected leaves of the tolerant hybrid compared with Cleopatra, the susceptible citrus genotype.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to callose deposition, we found that transcripts encoding a cytochrome P450 (CYP83B1), an enzyme involved in glucosinolate biosynthesis, were four-fold induced in the microarray analysis. Transcripts encoding a CYP83B1 were upregulated in symptomatic flavedo of citrus fruits upon CaLas infection [18]. Indole glucosinolates (IGs) are secondary metabolites derived from tryptophan, which have a well-characterized role in insect resistance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis has been used to successfully identify how Las infection influences gene expression in citrus plants on a global scale. 9,32,33 In particular, extensive changes in gene expression were identified for major biological processes such as stress responses, signal transduction, transport, cell organization and carbohydrate metabolism. 34 From a bacterial prospective, several proteins have been identified as important for virulence and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Sourcesink disruption and weak plant immunity response were the main mechanisms of disease. But, it showed that HLB symptom development depended on host response rather than on carbohydrate starvation from the microarray data by comparing fruits from HLB infected sweet orange and girdled fruit [30].…”
Section: Can Crispr Win the Battle Against Huanglongbing?mentioning
confidence: 99%